Primulina jiangyongensis (Gesneriaceae), a new species from Southern Hunan, China - Li, Ming; Yu, Xun-Lin; Ma, Qi-Xia (Phytotaxa, 2014)
A new species, Primulina jiangyongensis (Gesneriaceae) from limestone areas in southern Hunan, China, is described and illustrated. The new species differs from other species of Primulina mainly by its yellow corolla, with the lower lip having several dark purple stripes, peduncle and bracts densely spreading villous, pedicel densely glandular-villous, and filaments dark purple. According to the IUCN Red List Criteria, P. jiangyongensis is assessed as Critically Endangered (CR B2a; C2b) because of its limited populations and vulnerable habitat.